The Influence of Mother Tongue on Phoneme Pronunciation in Speaking Mandarin for IX Grade Students of SMP Tunas Bangsa Makassar - R., Sarah; Mantasiah R; Junaeny, Arini; Li, Yanyan (Journal of Chinese Language and Culture Studies, 2024)
This research is a qualitative descriptive study that aims to obtain data on the influence of mother tongue on the pronunciation of phonemes in speaking Mandarin for class IX students of SMP Tunas Bangsa Makassar. The data of this research is the pronunciation of segmental phonemes including consonants and vowels in Mandarin. The research data was obtained through audio recordings related to the oral test activities carried out by students. The data that has been obtained is then analyzed using an assessment table, conversion table and Foreign Service Institute table. From the results of data analysis, it is known that there is an influence of mother tongue on the pronunciation of phonemes in speaking Mandarin for class IX students of SMP Tunas Bangsa Makassar by obtaining FSI 1+ level, namely in the category of students being able to initiate and follow conversations and socialize on a limited basis.